2022
DOI: 10.1007/s00192-022-05077-w
|View full text |Cite
|
Sign up to set email alerts
|

Three-year follow-up of a self-administered Australian pelvic floor questionnaire validated in Chinese pregnant and postpartum women

Abstract: Introduction and hypothesis The aim of this study was to verify whether the Chinese version of the self-administered Australian Pelvic Floor Questionnaire (APFQ) can assess the changes in symptoms over a long time period (responsiveness) and to verify the reliability and validity of the questionnaire after 3 years of follow-up. Methods The questionnaire was completed by 146 women using the WeChat platform after 3 years of follow-up. Reliability was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
2
Order By: Relevance
“…The internal consistency in the APFQ-Sp showed a Cronbach's α of 0.972, and, in the sub-scales, it ranged between Cronbach's α = 0.828 (sexual activity section) and 0.935 (urinary tract section) (Table 3 ). These values are slightly higher than those observed in the Arabic (0.877) 21 , Chinese (0.83–0.89) 20 , 40 , Serbian (0.822–0.846) 19 , Turkish (0.733–0.858) 22 and original version (0.74–1.00) 18 , although all except one dimension from the Turkish version and one from the original version are considered to have excellent internal consistency 36 .…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…The internal consistency in the APFQ-Sp showed a Cronbach's α of 0.972, and, in the sub-scales, it ranged between Cronbach's α = 0.828 (sexual activity section) and 0.935 (urinary tract section) (Table 3 ). These values are slightly higher than those observed in the Arabic (0.877) 21 , Chinese (0.83–0.89) 20 , 40 , Serbian (0.822–0.846) 19 , Turkish (0.733–0.858) 22 and original version (0.74–1.00) 18 , although all except one dimension from the Turkish version and one from the original version are considered to have excellent internal consistency 36 .…”
Section: Discussioncontrasting
confidence: 61%
“…When the test–retest values are compared, since the APFQ-Sp has ICC values that range between 0.596 and 0.960 (Table 3 ), it is observed that they are consistent with the Arabic version 21 , which presents ICC values: 0.500–0.833. However, these values are slightly lower than those observed in the Serbian (ICC: 0.896–0.944) 19 , Turkish (ICC: 0.876–0.954) 22 , and original version (ICC: 0.74–1.0) 18 , and greater than some dimensions of the Chinese version (ICC: 0.22–0.88) 20 , 40 .…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations